2016
DOI: 10.1093/treephys/tpw024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mistletoe removal on growth, N and C reserves, and carbon and oxygen isotope composition in Scots pine hosts

Abstract: Most mistletoes are xylem-tapping hemiparasites, which derive their resources from the host's xylem solution. Thus, they affect the host's water relations and resource balance. To understand the physiological mechanisms underlying the mistletoe-host relationship, we experimentally removed Viscum album ssp. austriacum (Wiesb.) Vollmann from adult Pinus sylvestris L. host trees growing in a Swiss dry valley. We analyzed the effects of mistletoe removal over time on host tree growth and on concentrations of nonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 97 publications
2
30
0
1
Order By: Relevance
“…This is in agreement with previous observations in various understory species (Hommel et al 2014;Yan et al 2016). Moreover, Hommel et al (2014) also observed that drought could have stronger effects on assimilation rate than on stomatal conductance, thus potentially explaining the increase in Δ 13 C upon drought in grasses in late summer 2013 (Fig.…”
supporting
confidence: 92%
“…This is in agreement with previous observations in various understory species (Hommel et al 2014;Yan et al 2016). Moreover, Hommel et al (2014) also observed that drought could have stronger effects on assimilation rate than on stomatal conductance, thus potentially explaining the increase in Δ 13 C upon drought in grasses in late summer 2013 (Fig.…”
supporting
confidence: 92%
“…Leaf carbon components decreased at the end of growing season in order to maximize resource allocation, i.e., during leaf senescence, recycling nutrients from assimilating leaves back to storage organs (Chapin et al 1990). Stored resources may support new leaf and shoot growth after dormancy (Yan et al 2016), as well as defense and reproduction (Chapin et al 1990). Many studies have shown that leaves play a major role in resources remobilization (Millard 1996, Eckstein et al 1998, Cherbuy et al 2001.…”
Section: Resource Remobilization In Quercus Aquifolioides and Betula mentioning
confidence: 99%
“…While mistletoe leaves are capable of photosynthesizing and producing basic sugars, they typically have lower photosynthesis rates than their hosts, and many mistletoe species acquire large amounts of heterotrophic carbon from the host phloem sap to allow expansion of the mistletoe leaf area ( This reduces carbon availability for the host tree, which leads to reduced growth rates and reductions in host leaf biomass (Meinzer et al 2004, Rigling et al 2010, Agne et al 2014, Raftoyannis et al 2015. Such degradations of the host canopy will further reduce carbon assimilation rates and deplete the non-structural carbohydrate reserves of the host tree (Rigling et al 2010, Yan et al 2016).…”
Section: Carbon and Nutrient Cyclingmentioning
confidence: 99%